Precut technique using an injection needle: A retrospective study on a new ancillary procedure for pleural biopsy. Issue 31 (5th August 2022) - Mizumori, Yasuyuki; Hirano, Katsuya; Hirata, Nobuya; Hiraoka, Ryota; Takahashi, Sayaka; Kominami, Ryota; Miyake, Kohei; Takenouchi, Masaki; Kato, Tomohiro; Kume, Sachie; Higashino, Sachiko; Nakahara, Yasuharu; et al.
Abstract : The effectiveness of thoracoscopic biopsy as a diagnostic method for pleural diseases has been reported; however, obtaining a sufficient specimen size is sometimes difficult. Therefore, an ancillary technique, the precut technique using an injection needle, was devised to address this problem. This study aimed to evaluate the effectiveness and safety of the novel precut technique in patients with undiagnosed pleural effusion. This retrospective study included 22 patients who underwent pleural biopsy using the precut technique to examine exudative pleural effusion of unknown etiology. Thoracoscopy was performed under local anesthesia. The biopsy procedure was performed as follows: a needle was inserted into the pleura around the lesion using a semiflexible thoracoscope; the needle was positioned to make an incision in the pleura while injecting 1% lidocaine with epinephrine and lifting the pleura from the fascia; 2 or 3 precut incision lines were arranged in a triangle; and the specimen was obtained from the parietal pleura using forceps or a cryoprobe. Patient data including age, number of biopsies, biopsy specimen size, pathological and final diagnosis, and postoperative complications were examined. All patients were male with an average age of 74 years. Pleural effusion was found on the right and left sides in 16 and 6 patients, respectively. The average major axis of the biopsy specimens was 18 mm (range, 10–30 mm), which was sufficient to establish a pathological diagnosis. Only 1 patient experienced minor temporal bleeding as a complication. The precut technique enabled the procurement of specimens sufficient in size for pleural biopsy.